Hyperparathyroidism in Pregnancy Leading to Pancreatitis and Preeclampsia with Severe Features - Andrew G. Dale; Bradley D. Holbrook; Lauren Sobel; Valerie J. Rappaport (Hindawi Limited, 2017)
Background. Hyperparathyroidism is underdiagnosed in pregnancy, yet early diagnosis is necessary for the potentially severe sequelae of hypercalcemia for both the woman and fetus. Case. A 31-year-old, gravida 3, para 0-0-2-0 at 32 weeks and 3 days of gestation, presented with preeclampsia with severe features concomitant with acute pancreatitis and known diabetes mellitus type 2. She was stabilized and delivered. In the postpartum period, her total calcium level remained elevated. Ionized calcium levels and parathyroid hormone levels were also elevated, and she was diagnosed with hyperparathyroidism. Conclusion. Hyperparathyroidism and hypercalcemia are risk factors for pancreatitis. Women who develop pancreatitis during pregnancy are at increased risk of developing preeclampsia. If elevated serum calcium is noted, it should be confirmed with ionized calcium level and parathyroid hormones as ionized calcium levels are unaffected by pregnancy.